PENGARUH PENERAPAN STRATEGI DOMINO GAME DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI SMKN 4 PADANG - Citra Resmi, Dina; Rismen, Sefna; Harisman, Yulyanti (Pendidikan Matematika, 2014)
ABSTRACTThe research were motivated by the fear of asking students and issue an opinion on the matter is not yet comprehension and studentsâ comprehension of mathematical concept that still low. This study aims to assess the development of the math concept comprehension and determine whether the student math concept comprehensionÂ  by implementing strategies Domino Game accompanied quiz better math concept comprehension that students using conventional teaching class XI student of SMKN 4 Padang. This was an experimental research which used random to subject. Hypothesis test used Mann-Whitney with minitab software, obtained that P-value smaller than Î±, 0,0005 < 0,05 so hypothesis is accepting. The researcher concluded that of student math concept comprehension by implementing strategy Domino Game with Quiz better than of student math concept comprehension by implementing conventional learning in class XI SMKN 4 Padang.